METODE KISAH DALAM AL-QUR’AN DAN SUNNAH DAN URGENSINYA DALAM PENDIDIKAN KARAKTER - Bunyanul Bunyanul (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2019)
ABSTRACT وَأَنْ لَوِ اسْتَقَامُوا عَلَى الطَّرِيقَةِ لَأَسْقَيْنَاهُمْ مَاءً غَدَقًا“Dan bahwasanya: Jikalau mereka tetap berjalan Lurus di atas jalan itu (agama Islam), benar-benar Kami akan memberi minum kepada mereka air yang segar (rezki yang banyak)”. (Q.S. Al-Jin : 16)            It is undeniable that education is a process that is very important and even most important for humans to achieve the degree of glory in the eyes of Allah SWT and all His creatures. But the education process is not an easy thing, even education is a complex process because it is a planned, systematic, structured effort and aims to develop, manage, foster, direct, and change humans who are multidimensional beings towards perfection. The process of education is the process of "transferring" or transferring knowledge from the source of knowledge contained within explanations and information, the nature of things, and values that are useful for human life. So important is the value of science for humans that the most appropriate way is needed in the transfer process. The Fiqh Rule says, Ma La Yatimmul Obligatory Illa Bihi Fahuwa Obligatory, this means that if Science is very important and compulsory to be studied, then the media that causes that knowledge is acquired is equally important and mandatory. On this basis, education experts formulate strategies and appropriate methods that are in accordance with the basic character and human psyche. Then came the so-called method, uslub or tariqah in education. The method according to the Indonesian dictionary is interpreted as a systematic way of working to facilitate the implementation of an activity in order to achieve the specified goals. And the education method is defined the way or education system used by educators for the success of students to become noble human beings. Among the various methods of Islamic education that are recognized by scholars and education experts as a method of education based on the Qur'an and Sunnah is the Story method. Lots of Qur'anic verses that come down with the form of a story. Similarly, the texts of the hadith of the Prophet Muhammad. This paper will provide an explanation of the story method used in the Qur'an and the Hadith, the value of the educational philosophy contained therein, the power of the story method in moral education, and the urgency of the story method for character education.Keywords: Story In The Qur'an And Sunnah, Character Education